2009
DOI: 10.1021/es902482b
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Screening Analysis of Halogenated Norbornene Flame Retardants in the Laurentian Great Lakes: Dechloranes 602, 603, and 604

Abstract: Dechlorane (Dec) 602, Dechlorane (Dec) 603, Dechlorane (Dec) 604, and Dechlorane Plus (DP) are flame retardant substitutes for mirex. Dec 602, 603, and 604 were detected in sediment and fish from the Laurentian Great Lakes. Lake Ontario surface sediments had the highest concentrations of Dec 602 and 604 at 6.0 and 4.0 ng/g dry weight, respectively. Temporal analysis of a Lake Ontario sediment core indicates that Dec 602 and 604 trends are similar to DP peaking in the early 1980s. Lake trout and whitefish from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
183
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(214 citation statements)
references
References 18 publications
29
183
0
2
Order By: Relevance
“…Even lower MDL values were obtained in fish (pg g −1 lw) when using GC-NCI-MS/MS and GC-EI-HRMS (Barón et al, 2012;Shen et al, 2010Shen et al, , 2011a, which guaranteed the detection of DP with lower levels in the background areas.…”
Section: Instrumental Analysis and Quantificationmentioning
confidence: 90%
See 3 more Smart Citations
“…Even lower MDL values were obtained in fish (pg g −1 lw) when using GC-NCI-MS/MS and GC-EI-HRMS (Barón et al, 2012;Shen et al, 2010Shen et al, , 2011a, which guaranteed the detection of DP with lower levels in the background areas.…”
Section: Instrumental Analysis and Quantificationmentioning
confidence: 90%
“…EI mode was not recommended since an intense ion at m/z 270 (C 5 Cl 6 + ) will be formed in retro-Diels-Alder fragmentation, which may make the intensity of molecular ion low or even absent (Feo et al, 2012;Sverko et al, 2010b). Even so, there were many successful measurements conducted by monitoring the 271.8102/273.8072 ions using EI in HRMS (Brasseur et al, 2014;Shen et al, 2010Shen et al, , 2011aShen et al, , 2011b.…”
Section: Instrumental Analysis and Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Dechlorane 602, 603, and 604 were first reported in sediment and fish of the Great Lakes and their tributaries. 39,40 Wang et al reported Dechlorane 602 in soil and air in eastern China close to a production facility with atmospheric concentrations of ∼5 pg m À3 , 41 and Jia et al observed Dechlorane 602 and 603 in marine coastal sediment and oysters from China Sea indicating emissions of these compounds into the marine environment. 42 This is the first finding of these Dechloranes in the marine atmosphere.…”
Section: ' Introductionmentioning
confidence: 99%